2015
DOI: 10.1002/humu.22785
|View full text |Cite
|
Sign up to set email alerts
|

Lynch Syndrome Associated with Two MLH1 Promoter Variants and Allelic Imbalance of MLH1 Expression

Abstract: Lynch syndrome is a hereditary cancer syndrome caused by a constitutional mutation in one of the mismatch repair genes. The implementation of predictive testing and targeted preventative surveillance is hindered by the frequent finding of sequence variants of uncertain significance in these genes. We aimed to determine the pathogenicity of previously reported variants (c.-28A>G and c.-7C>T) within the MLH1 5′untranslated region (UTR) in two individuals from unrelated suspected Lynch syndrome families. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…[] showed that there was a complete loss of MMR when MLH1 or MSH2 mRNA were reduced to 25% of control cell levels [Kansikas et al., ]. This would be the in vivo equivalent of a 50% loss of expression from a variant allele combined with LOH in a tumor, suggesting that a 50% reduction or greater in promoter activity may be an ideal cutoff to define abrogated allele‐specific expression, as proposed previously [Green et al., ; Hesson et al., ].…”
Section: Laboratory Assays and Online Resources To Assess The Pathogementioning
confidence: 73%
See 1 more Smart Citation
“…[] showed that there was a complete loss of MMR when MLH1 or MSH2 mRNA were reduced to 25% of control cell levels [Kansikas et al., ]. This would be the in vivo equivalent of a 50% loss of expression from a variant allele combined with LOH in a tumor, suggesting that a 50% reduction or greater in promoter activity may be an ideal cutoff to define abrogated allele‐specific expression, as proposed previously [Green et al., ; Hesson et al., ].…”
Section: Laboratory Assays and Online Resources To Assess The Pathogementioning
confidence: 73%
“…There are no strict criteria in place for the size of the genomic region that should be investigated to exclude other co‐segregating pathogenic alterations. In previous studies, we sequenced a 10 kb region from the 3′ end of EPM2AIP1 to MLH1 exon 2 to exclude a genetic cause for an epimutation [Sloane et al., ] or performed targeted enrichment and sequencing of a 1.7 Mb region encompassing 15 genes across the MLH1 locus [Hesson, et al., ]. Moreover, Kwok et al.…”
Section: Laboratory Assays and Online Resources To Assess The Pathogementioning
confidence: 99%
“…In a reporter assay, variant c.-27A was designated to be causative for the reduced expression 16. Furthermore, promoter variants may also have regulatory effects without coincidence of methylation, as assumed, for example, for MLH1 promoter variants c.-11C>T, c.-42C>T and c.-413_-411delGAG reducing the promoter activity in varying degrees in luciferase reporter assays,25 26 and for variants c.-28A>G and c.-7C>T found in individuals with a partially reduced MLH1 gene expression 27…”
Section: Introductionmentioning
confidence: 99%
“…Many of the variants identified by GWAS are in fact located outside coding regions [90]. Also, variants implicated in Mendelian cancer syndromes may not necessarily be coding, examples of which include mutations in the MLH1 5’UTR region associated with CRC [159, 160] and presumed enhancers that may affect the expression of EPCAM - MSH2 read-through transcripts associated with CRC in EPCAM deletion carriers [161]. Likewise, a 40-kb duplication upstream of GREM1 has been linked to hereditary mixed polyposis syndrome by effecting an increased and ectopic expression of the BMP antagonist GREM1 [48].…”
Section: Guidelines For Gene Discoverymentioning
confidence: 99%